Conforto térmico de habitações em função do padrão construtivo - Silva, Antonio Marques da (2010)
One searched from the monitoring of you beached a ship ambient to evaluate the thermal comfort in the inside of habitations in function of the constructive standard and of its disposals in the geographic and urban physical space. The methodology followed in the research proposal allowed that the slum quarter selected for such study was the Slum quarter of Canvas, situated in the Eustáquio Gomes Quarter, the City of Maceió, the State of Alagoas, for also presenting particularity in the arrangement of its habitations and in the constructive profile of these, beyond its disposals in improvised the urban space, come if to show as segregated urban scene when compared with immediate its around. Two habitations of black canvas and one of masonry of conventional, situated standard had been selected constructive next the slum quarter habitations, not being this third considered typical one of slum quarter. Where in them they had been installed in its interiors dataloggers, that they had allowed to monitor in the period of 01 the 31/03/2007, to collect temperatures and internal relative humidity of air that allowed to understand the dynamics evaluative of its internal microclimates, being complemented to this study the temperatures collected in the exterior of these, given meteorological relative to the deriving Maceió city of the Meteorological Station of the Zumbi of Palmares Airport in Maceió, And also of the shelter installed in the exterior of the analyzed habitations. According to given conclusive: all the habitations if had presented with levels of comfort in a platform that indicated inexistence of any type of comfort, the masonry habitation total presented it a comparative bigger thermal isolation with the habitations of black plastic canvas and of black canvas and the asbestos cover, that is, less vulnerable to the external thermal variation, had the biggest thermal resistance of the constituent materials of this typology, on the other hand, the consisting habitation total of black canvas presented critical levels of very intolerable discomfort and the habitability in more than 75% of the analyzed hours due the inefficiency of the arrangement and configuration architectural, low inertia and thermal resistance and form of use that it became the habitation with the greenhouse profile, for confining hot air in its interior. Habitation 2, of black canvas and asbestos cover, was presented total uncomfortable but, less uncomfortable if compared with the coated one with black canvas, since the same one took off advantage of the geographic orientation, the use of vegetation in around of the inexistence of internal walls providing the existence of the crossed ventilation, overlapping cardboard use the internal faces of the walls come to confer a thermal inertia bigger if compared with the habitation 1 and thermal retardation of its constructive materials, being this more tolerable construction the habitability. One expects that in research subsequent to this, can be more used other meteorological parameters and other diversities of consisting habitations of constructive materials with distinct characteristics and the use of instruments of collections sophisticated, that allow to represent faithful and to interpret the real situation of the evolution dynamic of internal and external microclimates of the habitations white of the research, the point of being able to intervene in the space constructed and inhabited of form to guarantee levels of comfort to its users.